FIQH, SYARI'AH, DAN PERBEDAANYA - Harun Abdullah (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2022)
Abstract:Â Islamic law is actually nothing other than Islamic fiqh or Islamic law, which is applied according to the needs of the community which is sourced from the Qur'an As-Sunnah and the consensus of friends and tabi'in. Shari'a itself is a revelation of Allah and the words of the Prophet, are the legal foundations established by Allah through His Messenger, which must be followed by Muslims.